Financial analysis of the Russian forest product companies - Sokolov, Stanislav (2008)
The thesis applies financial analysis and assesses the financial performance of six Russian forest product companies, i.e. evaluate how well the companies perform. The goal is achieved through implementation of different financial analysing tools and techniques, mainly financial ratio analysis. Different financial measures are evaluated. Furthermore, comparisons are made between companies, their past and expected future development is analysed and compared with the economy in general. Ratio analysis showed as well that all studied companies had problems with the absolute liquidity. However, other types of financial liquidity were at acceptable levels. Profitability of studied companies was poor for majority of businesses. It was connected with low returns on assets and inadequate profit margins. Activity ratios that define the companies' market strategies had more or less good figures. According to ratio analysis of financial leverage, the studied companies were divided in two groups - financially independent businesses and others that rely on external funding.